Indian Software Industry: The Challenges and Opportunities - Mane, Santosh (2008)
To date, there has been vast discussion about two important issues namely, the challenges and opportunities of Indian IT-ITES industry. But as industry makes progress, challenges faced by the industry are different and keep changing time to time. Same is the case of Indian software industry. After independence from British rule, India for decades was much closed economy, due to the unstable geopolitical environment the required attention was not given towards the development of the country. IT industry in India begun in 1970s, but the challenges at that time were different from the challenges of 1990s. Also, the challenges of 1990s were different from the challenges faced by industry at recent. Indian software industry has seen initially a slow but fast later growth. Initially as a starter there were tremendous challenges, but if challenges are handled properly they come infront as opportunities.